Efeitos da peçonha da cascavel (Crotalus durissus terrificus) em rim isolado de rato - Silva, Ivany Maria do Socorro Carvalho da (1995)
Acute renal failure seems to be the chief cause of morbidity and mortality of people poisoned by Crotalus durissus terrificus. The technique of isolated kidney of rat is a useful model for the study of direct effect of drugs on the renal function. In this work we have used this techinique to investigate the effect of Crotalus durissus terrificus venom and crotoxin, as principal fraction of it. The experiments were carried out in five groups of kidney which were perfused with: 1) albumin 6g% (control albumin); 2) crotoxin l^g/ml; 3) crotoxin 2//g/ml; 4) venom l^g/ml; 5) dexametasone 10/íg/ml + venom l//g/ml. The wistar rats were anesthetized with pentobarbital in a dosis of 50mg/Kg of body weight. A distai canulation of the right ureter was performed and subsequatly of the renal artery. After this procedure, a nephectomy of the right kidney was done. The kidney was coupled to the perfusion system. After a stabilisation period (20 min) of the preparation, the first sample of the perfusate was colleted (Po). From Po, samples of urine and perfusate were collected every 10 minutes, besides the measure of urinary volume and of the perfusion pressure. These samples were analysed to determine the contents of sodium and potassium ions and osmolality. The duration of the experimental was of 90 to 120 minutes. The substances tested were put in the perfusion system after 30 minutes from Po. In the group dexametasone + venom, the corticosteroid was put into the system in 30 minutes, and the venom in 60 minutes. After the experiment the not perfused left kidneys and the right kidneys had their humid and dry weight calculated, as well as their content of tissular sodium and potassium. Using the experimental data we have calculated the following parameters: urinary flow, rate of glomerular filtration, filtrated sodium, excreted sodium, transported sodium, percentage of reabsorbed sodium, filtrated potassium, excreted potassium, transported potassium, percentage of transported potassium, osmotic clearance, free water clearance, distai transport of sodium, percentage of distai transport of sodium, proximal transport of sodium, percentage of proximal transport of sodium.